What’s wrong with ’technology enhanced learning’? - Bayne, Siân (Proceedings of the International Conference on Networked Learning, 2014)
In recent years, ’technology enhanced learning’, or ’TEL’, has become a widely-accepted term in the UK for describing digital incursions upon higher education, to a large extent taking the place of other recently-popular terminologies such as ’e-learning’, ’learning technology’ and ’computer-based learning’. Yet there has been little critique in the literature of the fundamental assumptions embedded within the terminology of TEL: rather it has been adopted as an apparently useful, inoffensive and descriptive shorthand for what is in fact a complex and often problematic constellation of social, technological and educational change. In their paper reviewing interpretations of ’TEL’ in the existing literature, Kirkwood and Price (2013) emphasise the tendency to use the term in an ’unconsidered and unreflecting’ way (4), making a sound attempt to provide some clarity by synthesising the various tacit conceptions of enhancement in existing research in educational technology. In this brief paper, I will approach the issue rather differently, by subjecting the term itself to a critique, drawing on insights from science and technology studies, critical posthumanism and Biesta’s (2005) critique of the ’learnification’ of education. In doing so, my aim is to begin to question the widespread buy-in to the term by researchers, practitioners and policy-makers. I aim to argue that ’TEL’, far from being an unexceptionable and neutral term simply in need of clearer definition, is in fact a deeply conservative discourse which reduces our capacity to be critical about digital education, and fails to do justice equally to the disruptive, disturbing and generative dimensions of the academy’s enmeshment with (digital) technology. As an alternative, I conclude with an overview of the ways in which critical posthumanism might inform a richer understanding of the issues at stake, suggesting that we need to be more careful with, and more critical of, the terminology we adopt to describe and determine the field of digital education.